KEY FEATURES OF TERMINOLOGY SYSTEMS IN THE SOCIO-ECONOMIC DOMAIN - Ayaqulov Nurbek Abdug‘appor o‘g‘li; Xidirov Olmosbek Abdurazak o‘g‘li (Journal Park Publishing, 2024)
This article emphasizes the importance of studying term elements as linguistic units possessing “dual systematicity.” These elements exhibit all the characteristics of words in the standard literary language and can fulfill any functions typical of a word.
Keywords: terminological systems, pragmatic meaning, cognitive-discursive approach, metaphorical rethinking, dual systematicity, evaluative terminology.